Language Anxiety in Online Japanese Speaking Learning: Study on Beginner Level of Japanese Language Students - Muliadi, Muliadi; Danasasmita, Wawan; Widianti, Susi (Journal of Japanese Language Education and Linguistics, 2022)
Anxiety in the language classroom is an affective filter that interferes with input from being used for language acquisition (Krashen, 1982). Moreover, Ellis (2015) stated that anxiety could cause poor learning outcomes. This study aims to investigate 1) level of language anxiety in beginner level of Japanese language students in online learning situations; 2) relation between language anxiety and self-perception; 3) relation between language anxiety and speaking-based learning outcomes; 4) relation between self-perception and speaking-based learning outcomes, and 5) the sources of language anxiety. A survey was administered to 149 Japanese language students from two state universities in Sumatra. There were 67 students in their first year and 82 in the second year. About 20 students participated in the interview. This study adopted the Japanese language anxiety scale developed by Motoda (2000) to measure anxiety level and used the self-perception scale developed by Kitano (2001) to measure students’ perception of speaking ability. The study found that language anxiety in online learning situations was high. Correlation analyses showed a negative correlation between language anxiety and self-perception. If the level of anxiety rises, self-perception will decrease. Meanwhile, there was a positive correlation between self-perception and student speaking-based learning outcomes. Then, if self-perception increases, student outcomes will increase. There was no correlation between anxiety and speaking-based learning outcomes. The study identified that anxiety in online learning activities stems from personal and interpersonal anxiety, beliefs about teachers, classroom procedures, interaction activities, aspects of infrastructures, and aspects of the language test.